The Effectivity of Therapeutic Communication on Pre-Surgery Education of The Implementation of Phacoemulsification technique Cataract Surgery With Local Anesthesia - Diyah Arini; Christina Yuliastuti; Aziza Nafi (IJECA (International Journal of Education and Curriculum Application), 2019)
Surgery, whether it is elective or emergency, is a complex event that triggers stress both on the patient and the family. Not only extending the surgery wait time, postponing or cancelling the surgery could increase the severity of the cataract that may result in blindness. This research goal is to know the effectivity of therapeutic communication on the implementation of cataract surgery. This research uses Pre-Experimental design with Post Test Only Control Group approach. A population of 176 respondents will be scheduled for cataract surgery to meet the inclusion criteria. The sampling technique is using simple random sampling technique and 64 respondents are divided into control and intervention groups. The data analysis is using Paired Sample T-test statistical test. The research result shows that almost all of the respondents who continue to the surgery with a number of 30 respondents (93,8%) and the number of respondents who postpone the surgery is only 2 respondents (6,2%), while those who implements daily communication shows that 22 respondents (68,8%) continue to the surgery and the 10 respondents (34,2%) postpone the surgery. The result of Paired Sample T-test statistical test shows that P value = 0,003 < 0,05 means that there is a difference in the surgery between the intervention and the control group. The implications of this research can be applied by nurses to be more creative and innovative, professional and skilled in applying therapeutic communication when providing pre surgery cataract education.